Correlation between changes in intraocular pressure and refractive error indices post Cataract Surgery: IPO and refractive error indices post Cataract Surgery - Bodla, Muhammad Afzal; Bodla, Ali Afzal; Moazzam, Ayema; Tariq, Noor (Pakistan Journal of Medical Sciences, 2020)
Objective: To evaluate the correlation between refractive errors and change in intraocular pressure in patients undergoing cataract surgery. Methods: This interventional retrospective case study was carried out from September 2018 to April 2019 at Bodla Eye Care and Multan Medical and Dental College, Multan. A total of 127 eyes were recruited in the study among which six were excluded. Out of remaining 121, 53 eyes were emmetropes, 41 were mild myopes and 27 were high myopes. Single surgeon performed the procedure. Pre-operative investigations of IOP and refractive error were done by goldmann tonometry and auto refractometry. IOP was reviewed at day 1, 7, 14 and 28 post cataract surgeries. Results: Out of 121 eyes, 53 eyes were emmetropes, 41 were mild myopes and 27 were high myopes, who underwent phacoemulsification. There was an elevation of 2-3mm Hg at Day-1, in emmetropes and mild myopes, and further on, a constant drop was noticed on follow ups. In high myopes a significant fluctuation of IOP was noted in first fourteen days followed by an unremarkable gradual decline afterwards. Conclusion: Cataract surgery helps lowering the IOP in patients with refractive errors. Mild myopic and emmetropic patients showed a linear swift pattern while high myopes presented instable and gradual reduction in IOP. A total decrease of 1-2mm Hg was seen at the end of the study depicting that relation between IOP and cataract surgery is insignificant. doi: https://doi.org/10.12669/pjms.36.3.1597 How to cite this: Bodla MA, Bodla AA, Moazzam A, Tariq N. Correlation between changes in intraocular pressure and refractive error indices post Cataract Surgery. Pak J Med Sci. 2020;36(3):574-577. doi: https://doi.org/10.12669/pjms.36.3.1597 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.